2022
DOI: 10.1021/acs.langmuir.2c02553
|View full text |Cite
|
Sign up to set email alerts
|

Physical, Electrochemical, and Solvent Permeation Properties of Amphiphilic Conetwork Membranes Formed through Interlinking of Poly(vinylidene fluoride)-Graft-Poly[(2-dimethylamino)ethyl Methacrylate] with Telechelic Poly(ethylene glycol) and Small Molecular Weight Cross-Linkers

Abstract: We report the preparation of dense and porous amphiphilic conetwork (APCN) membranes through the covalent interconnection of poly(vinylidene fluoride)-graft-poly[(2-dimethylamino)ethyl methacrylate] (PVDF-g-PDMAEMA) copolymers with telechelic poly(ethylene glycol) (PEG) or α,α-dichloro-p-xylene (XDC). The dense APCN membranes exhibit varying solvent swelling and mechanical properties depending on the compositions and overall crystallinity. The crystallinity of both PVDF (20−47%) and PEG (9–17%) is significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…However, the presence of the cross-links or/and the nonideal structure of the APCN building blocks lead to the formation of frustrated/distorted morphologies, with much less regularity than the morphologies observed with (non-cross-linked) linear block copolymers . Thus, the APCN electron micrographs or atomic force micrographs usually exhibit morphologies with spheroidal domains, and the corresponding small-angle X-ray scattering (SAXS) or small-angle neutron scattering (SANS) profiles present a single broad peak. ,, However, recent synthetic developments, involving sparser and more regular cross-linking, e.g., end-linking, as well as the utilization of near-ideal building blocks (well-defined linear or star polymers), resulted in APCN nanophase-separated morphologies of high regularity, e.g., wavy lamellae, and SAXS and SANS profiles with a number of higher order peaks. , The experimental recording of these more regular morphologies in self-assembled APCNs renders their modeling/simulation more worthwhile. In particular, current state-of-the-art simulations and self-consistent field theories (SCFT) very successfully reproduce the experimentally observed morphologies of linear diblock melts and are, consequently, expected to accurately predict the morphologies formed by APCNs comprising well-defined building blocks .…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of the cross-links or/and the nonideal structure of the APCN building blocks lead to the formation of frustrated/distorted morphologies, with much less regularity than the morphologies observed with (non-cross-linked) linear block copolymers . Thus, the APCN electron micrographs or atomic force micrographs usually exhibit morphologies with spheroidal domains, and the corresponding small-angle X-ray scattering (SAXS) or small-angle neutron scattering (SANS) profiles present a single broad peak. ,, However, recent synthetic developments, involving sparser and more regular cross-linking, e.g., end-linking, as well as the utilization of near-ideal building blocks (well-defined linear or star polymers), resulted in APCN nanophase-separated morphologies of high regularity, e.g., wavy lamellae, and SAXS and SANS profiles with a number of higher order peaks. , The experimental recording of these more regular morphologies in self-assembled APCNs renders their modeling/simulation more worthwhile. In particular, current state-of-the-art simulations and self-consistent field theories (SCFT) very successfully reproduce the experimentally observed morphologies of linear diblock melts and are, consequently, expected to accurately predict the morphologies formed by APCNs comprising well-defined building blocks .…”
Section: Introductionmentioning
confidence: 99%
“…This class of crosslinked networks swells both in water and organic solvents and maintains cocontinuous morphology. Structural investigation revealed that the components in an APCN matrix form nanophase morphology. APCNs find applications in controlled release of drugs, immunoisolatory devices, , ion exchange membranes, , Li ion transport membranes, specific protein binding matrices, antibiofouling/antifouling coating, and controlled release of antimicrobial agents. , APCNs are capable of activating biocatalysts in organic solvents …”
Section: Introductionmentioning
confidence: 99%